Arpeggion-H: Uma Interface Interativa para Reprodução de áudio MPEG-H - Moreira, Bruno Augusto R. de M.; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244092, 2024)
This paper provides an overview of the Arpeggion-H audio player, able to reproduce and interpret the metadata extracted from mhm1 encoded MP4 files, based on the MPEG-H part 3 norm. It is also able to display and alter the available configuration inferred from the audio’s metadata at any time. This tool will be useful to academic and common users, as it is able to play and allow user interaction out of a codec that is normally not supported. In the present implementation, this tool uses the decoder implement by the Fraunhofer-IIS group called “mpeghdec”, but it may support any other decoder if properly integrated.